Crystal‐clear days and unclear days in migraine: A population‐based study. Issue 7 (14th July 2022) - Lee, Wonwoo; Cho, Soo‐Jin; Hwang, Heewon; Lee, Myeongjee; Kim, Eun Hwa; Kim, Kyung Min; Heo, Kyoung; Chu, Min Kyung
Abstract: Objective: To investigate crystal‐clear days and unclear days in participants with migraine. Background: Migraine affects individuals during the headache‐free period. Therefore, headache‐free days do not indicate migraine symptom‐free days. Crystal‐clear days can be characterized by days without headache and having minimal or no migraine symptoms. In contrast, days without headache, but with more than minimal migraine symptoms, can be defined as unclear days. Methods: We used the baseline respondent data set of the Circannual Change in Headache and Sleep study, a nationwide population survey on headache and sleep. This study was a cross‐sectional and case–control analysis of longitudinally collected data. The number of crystal‐clear days per 30 days was assessed by asking "How many days have you had crystal‐clear days without headache during the previous 30 days?". We defined headache‐free, but not crystal‐clear days, as unclear days. The number of unclear days per 30 days was calculated as follows: 30 – the number of headache days per 30 days – the number of crystal‐clear days per 30 days. Results: Of 170 participants with migraine, 165 (97.1%) had unclear days. The numbers of crystal‐clear days (median [interquartile range] 20.0 [15.0–25.0] vs. 25.0 [20.0–29.0], p  < 0.001) and unclears days (4.0 [0.0–8.0] vs. 1.0 [0.0–7.0], p  < 0.001) per 30 days in participants with migraine were significantly lower and higher, respectively, than in those with non‐migraine headache. Headache days (incident rate ratio and 95% confidence interval, 0.94 [0.90–0.97], p  < 0.001) and weekly average sleep duration (0.95 [0.91–1.00], p  = 0.035) were significant factors for crystal‐clear days. Conclusions: The number of crystal‐clear days were different from that of headache‐free days. Almost all participants with migraine had unclear days. Our findings will facilitate understanding the symptoms and burden of migraine.